Time-dependent volume fraction of CdTe quantum dots in glass - Allahverdi, C.; Yukselici, M. H. (IOP PUBLISHING LTD, 2008)
CdTe quantum dots were grown in a borosilicate glass matrix by a two-step heat treatment process. Their average radius, size dispersion and number per unit volume (volume fraction) have been determined by using a simple absorption model based on the density matrix approach. The volume fraction of CdTe quantum dots in the strong confinement regime during normal growth stage is found to be proportional to the heat treatment time to the power of similar to 1.4. A very low dispersion of 4.79% was obtained at the end of 6 h of heat treatment at 590 degrees C.
Keywords: SIZE DISPERSION; PRECIPITATION; NANOCRYSTALS; EXCITONS; CDS; Physics